2013
DOI: 10.1128/aem.01812-13
|View full text |Cite
|
Sign up to set email alerts
|

prfA -Like Transcription Factor Gene lmo0753 Contributes to l -Rhamnose Utilization in Listeria monocytogenes Strains Associated with Human Food-Borne Infections

Abstract: e Listeria monocytogenes is a food-borne bacterial pathogen and the causative agent of human and animal listeriosis. Among the three major genetic lineages of L. monocytogenes (i.e., LI, LII, and LIII), LI and LII are predominantly associated with food-borne listeriosis outbreaks, whereas LIII is rarely implicated in human infections. In a previous study, we identified a Crp/Fnr family transcription factor gene, lmo0753, that was highly specific to outbreak-associated LI and LII but absent from LIII. Lmo0753 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Notably, despite expression of Pdu proteins, no production of pdu BMC signature metabolites propionate and 1-propanol was detected as shown above (figure 2), in line with our previously reported data [13], that showed only presence of BMCs and activation of pdu BMC in anaerobically rhamnose grown cells with added B12. Our data extend previous RNAseq studies that showed slight increase in pdu expression in the presence of propanediol, and highest expression when B12 was also present [28, 29]. The lack of pdu BMC activation in anaerobic MWB plus rhamnose conditions, suggests that the observed activation of B12 synthesis enzymes does not result in the production of sufficiently high levels of (de novo) B12 to trigger full induction (Figure 3A and Supplementary Table 5).…”
Section: Resultssupporting
confidence: 87%
“…Notably, despite expression of Pdu proteins, no production of pdu BMC signature metabolites propionate and 1-propanol was detected as shown above (figure 2), in line with our previously reported data [13], that showed only presence of BMCs and activation of pdu BMC in anaerobically rhamnose grown cells with added B12. Our data extend previous RNAseq studies that showed slight increase in pdu expression in the presence of propanediol, and highest expression when B12 was also present [28, 29]. The lack of pdu BMC activation in anaerobic MWB plus rhamnose conditions, suggests that the observed activation of B12 synthesis enzymes does not result in the production of sufficiently high levels of (de novo) B12 to trigger full induction (Figure 3A and Supplementary Table 5).…”
Section: Resultssupporting
confidence: 87%
“…Further, atypical strains with deficient rhamnose fermentation have been reported to be attenuated in virulence and have reduced resistance to temperature changes [45]. In contrast, L. monocytogenes serotype 1/2a mutants confer phage-resistance due to a loss of rhamnose.…”
Section: Discussionmentioning
confidence: 99%
“…Although the capability to degrade l -rhamnose is present in the genomes of many enteropathogens (), a role of this metabolic pathway in vivo remains to be elucidated. Recently, a novel transcription factor was identified in L. monocytogenes strains associated with foodborne infections and it could be demonstrated that this prfA -like regulator contributes to l -rhamnose utilization (Salazar et al , 2013).…”
Section: L-fucose L-rhamnose and Sialic Acidmentioning
confidence: 99%